Estresse acadêmico, fenômeno do impostor e coping na pós-graduação em administração - Araújo, Rafaela de Almeida (2020)
This research investigates the relationship between Academic Stress, the Phenomenon of the Impostor and Coping strategies within the context of graduate studies in Business School. For this purpose, it is used the theoretical basis of Lazarus and Folkman (1980), de Clance (1985) and Esparbès, Sordes-Ader and Tap (1993) to elucidate, respectively, Academic Stress, Impostor Phenomenon and Coping. The study is a quantitative and descriptive research, carried out with 535 students and professors of graduate studies in Business School in Brazil. Data analysis was performed using multivariate statistical techniques such as Pearson and ANOVA correlation analysis with the help of SPSS software - version 22. As a result, it is possible to state that stricto sensu graduate students in the Business School area have work overload as its main source of stress. Regarding the FI, the feelings of imposture are experienced in a moderate to intense degree by academics. A low correlation was found between Academic Stress and the Phenomenon of the Impostor, despite that, during the analysis of the difference between the averages (ANOVA), a low but constant increase was observed when it comes to this relation. Women suffer more from stress and FI. Regarding physical activities and religion, which are considered coping strategies, the majority of the sample who practices these activities have shown to suffer less from stress. As for the black minority, this group has shown to suffer more from both Stress and the Impostor Phenomenon as well as being the group who is more likely to use the negative coping strategies. Finally, considering the Coping strategies, a low correlation was found between both variables with the Isolation Strategies being more expressive for Academic Stress and Impostor Phenomenon, which are considered negative Coping strategies.